A web-based crowdfunding system for supporting social and community projects - Lau, Jie Shi (2025)
This project focuses on the development of online crowdfunding platforms for academic purposes. The aim of the project is to empower the social and community projects in Malaysia by enabling them to raise funds effectively. While platforms such as GoFundme, GoGetFuding, SimplyGiving and MyFundAction provide several essential features that improve user satisfaction, they also face significant limitations. These include a lack of feedback systems, lack of a sliding scale transaction fee structure and insufficient fee transparency which hinder platform usability. Even though previous studies explored various aspects of crowdfunding such as financial structure and user engagement, however, the operational and structural constraints of the platforms remain unexamined. To address these gaps, this study examines the limitations of existing platforms and proposes solutions for enhancements by implementing the feedback system, integrating the operation model, implementing the sliding scale method for fee structure and integrating fee transparency. Furthermore, the methodology of the project employs the Agile Software Development Life Cycle which facilitates incremental and iterative development by breaking the projects into small and manageable tasks. The project utilized several software components such as HTML, Javascript, CSS, PHP and MySQL to perform online crowdfunding platform development. The findings suggest that addressing the gaps can significantly enhance user satisfaction, trust and long-term sustainability of the platform. These outcomes are significant for platform developers, organizers and users who want to enhance the efficiency of community fundraising campaigns and crowdfunding experience for a wider audience. Ultimately, this research seeks to empower the social and community projects through a dedicated online crowdfunding platform in Malaysia.